EFEKTIVITAS PENGELOLAAN DANA KELURAHAN DALAM RANGKA PENINGKATAN SARANA DAN PRASARANA DAN PEMBERDAYAAN MASYARAKAT DI KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO - SEMPO, JORDAN SAPUTRA; LALOMA, ALDEN; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
Inadequate human resources are one of the factors inhibiting the maximum development program basedon these problems. This study aims to determine how Village Fund Management in the Context of ImprovingFacilities and Infrastructure and Community Empowerment in Shoulder Village, Malalayang District,Manado CityThis research is designed as a qualitative study with the intention of exploring or building a procession orexplaining the meaning behind reality. In this study, the data sources (informants) are employees who workin the Shoulder Village Government, starting from the Head of the Village, the Secretary of the Village, theGovernment Division of the Head of the Village, Heads of the Environment and Customary Figures,Community Figures, Religious Figures and all those involved in managing funds. sub-district. The datacollected in this study were processed and analyzed qualitatively using an interactive analysis modelThe results showed that in the planning stage, there was no provision for the distribution of what percentageof AAK was used for various existing community empowerment programs. This organizing stage isconsidered to have run well, because there has been a division of responsibilities to every institution thathas been formed in the Shoulder Village, and the institution has been running according to its mainfunction. Implementation Stage, Shoulder Village has a main problem, namely limited liquid funds. Limiteddisbursement of funds has made programs and activities, especially physical, not well realized. In addition,the demotivation of the community and a lack of interest in continuing their existing skills made the programineffective. The last stage is Supervision. In this dimension of supervision, includes reporting and62evaluation. However, in the evaluation aspect, it did not go well, this is because there was no evaluation thatwas carried out after the activity was carried out. In fact, evaluation plays an important role in makingfuture activities run better than before.Keywords: Effectiveness, Fund Management, Community Empowerment